2020
DOI: 10.1186/s12884-020-02897-w
|View full text |Cite
|
Sign up to set email alerts
|

Quality of consumer-oriented websites containing information about the second trimester ultrasound examination during pregnancy

Abstract: Background: Providing information about prenatal tests is a clinical challenge and the public frequently accesses the Web to read pregnancy-related information. The overarching aim of this study was to investigate the quality of consumer-oriented websites addressing obstetric ultrasound examination in the second trimester of pregnancy. Methods: Swedish websites were identified with Google, using 20 search strings and screening 400 hits (n = 71 included websites). Reliability and information about the examinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Like other examinations of online information relating to pregnancy, 19 , 20 , 21 this study found that the quality of the information about CMA and ES was rated as low overall and had been written at an advanced reading level. We also found that, although professional bodies have made recommendations on the content that should be included when providing information to parents about CMA 28 , 29 and ES, 30 , 31 , 32 there were several regularly occurring omissions.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…Like other examinations of online information relating to pregnancy, 19 , 20 , 21 this study found that the quality of the information about CMA and ES was rated as low overall and had been written at an advanced reading level. We also found that, although professional bodies have made recommendations on the content that should be included when providing information to parents about CMA 28 , 29 and ES, 30 , 31 , 32 there were several regularly occurring omissions.…”
Section: Discussionmentioning
confidence: 52%
“…41,42 We know that patients often search online for information while trying to understand and make decisions about genetic testing and, in the United Kingdom, pregnant women have reported searching in particular for texts written by medical professionals or published by medical institutions. 43 High-quality written Like other examinations of online information relating to pregnancy, [19][20][21] this study found that the quality of the information about CMA and ES was rated as low overall and had been written at an advanced reading level. We also found that, although professional bodies have made recommendations on the content that should be included when providing information to parents about CMA 28,29 and ES, [30][31][32] there were several regularly occurring omissions.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…This methodology was also used in three peer‐reviewed manuscripts published by the senior author and in publications on various medical topics including second trimester ultrasound examination, gender‐affirming hormone treatments, and rhinoplasty. 14 , 15 , 16 , 62 , 63 , 64 However, to reduce rating bias, it may have been more ideal to have two independent reviewers extract data with the DISCERN tool. The assessor was not blinded to the category of the website, which could introduce bias in the DISCERN assessment.…”
Section: Discussionmentioning
confidence: 99%